Exploring the Relationship Between Vocabulary Knowledge and Reading Comprehension Skills - Reza Khatami, Muhammad; Maulana Gibrani, Akbar; Suharyadi, Suharyadi (International Journal of Language Teaching and Education, 2026)
This study carries some practical implications for Indonesian EFL classrooms, particularly about the role of vocabulary in the improvement of reading comprehension, which could be useful for EFL teachers in designing successful lessons. The present study was conducted to investigate, in addition to the correlation of vocabulary skill and reading comprehension, whether vocabulary predicts reading performance. Accordingly, the quantitative correlational research design was employed in the study. Subjects were thirty-nine tenth-grade students from MA Daarul Ukhuwah. Students' receptive vocabulary was assessed with a 20-item vocabulary test. The school assessed reading level with an end-of-semester test. The Shapiro-Wilk tests suggested that the data were not normally distributed, and therefore, Spearman's rho correlation and simple linear regression analyzes were conducted to analyze the data. The correlation between rating comprehension and vocabulary knowledge was large and moderate (rs = .363, p = .023). Vocabulary knowledge was responsible for 12.4% of the variance in reading comprehension scores (R² = .124). From an educational point of view, the results suggest that instruction in contextualized vocabulary should be augmented by inferencing and building background knowledge to improve reading comprehension. Future studies should employ larger and more diverse samples, use item-level, psychometrically validated instruments, and employ more rigorous methods for calculating effect sizes to better inform classroom practice.